Building a Values-Driven Organization : - Barrett, Richard (Butterworth-Heinemann, 2006)
Richard Barrett, author of the best-selling book Liberating the Corporate Soul, presents his new thinking. Based on his experience working with over 1,000 organizations in 32 countries on cultural transformation for the values-driven organization. He presents a whole system approach to cultural transformation, showing organizations how they can change their culture to become values-driven organizations that support their employees, their customers, their partners, their leaders, and ultimately drive effectiveness and profit.